Comparison of 10-year overall survival between patients with G1 and G2 grade Ta bladder tumors. Issue 16 (April 2018) - Balan, Daniel; Martha, Orsolya; Chibelean, Calin Bogdan; Tataru, Sabin; Voidezan, Septimiu; Sin, Anca; Matei, Victor Deliu; Vartolomei, Mihai Dorin; Lucarelli, Giuseppe; Cioffi, Antonio; Del Giudice, Francesco; De Berardinis, Ettore; et al.
Abstract : Abstract: To compare long-term overall survival (OS) in patients with G1 and G2 grade Ta bladder cancer after transurethral resection of bladder tumors (TURBTs). Secondary aim was to investigate clinical and pathologic prognostic factors for OS of Ta patients, except G3/high grade (HG). A total of 243 patients, retrospectively selected, with Ta nonmuscle invasive bladder cancer (NMIBC) underwent TURBT between January 2006 and December 2008 (median follow-up 109 months). Inclusion criteria were: Ta at first manifestation, G1 or G2 grade with no associated carcinoma in situ (CIS). Seventy-nine patients were excluded due to concomitant CIS (1), G3/HG tumors (47), and lost to follow-up (31). Ethical approval was obtained from the Ethical Committee of the Mures County Hospital. Statistical analysis was performed using STATA 11.0. Following inclusion criteria, 164 patients with primary G1 or G2 Ta tumors, were enrolled. Recurrence was observed in 26 (15.8%) and progression in 5 (3%) patients. Ten-year survival in G1 patients was 67.8% (CI 54.3–78.1) and in G2 patients 59% (CI 49–67.3) ( P = .31). Univariable and multivariable logistic regression analysis underlined that advanced age at diagnosis (hazard ratio [HR] 1.10) and no Bacillus Calmette–Guerin (BCG) treatment (HR 0.24 and 0.29) were independent predictors for death at 10 years after diagnosis. Long-term analysis confirms that patients with well differentiated (G1) and moderately well differentiated (G2) Ta tumors have similar OS. A longer OS was even reported in those who underwent BCG adjuvant therapy.